A Study on National Girls Education Strategy Implementation, Monitoring and Evaluation - Rashid, Ruhee (American Journal of Education and Learning, 2017)
The purpose of this study to discuss the different national girl’s strategies that promotes the female education in Jammu & Kashmir. These strategies are important for female education. These strategies includes regional education bureaus, activities to be performed by technical and professional institutions, activities to be performed by central bodies, the role of mass-media, activities to be performed by higher education institutions etc. have been discussed.